High Percentage of ADAM-10 Positive Melanoma Cells Correlates with Paucity of Tumor-Infiltrating Lymphocytes but Does Not Predict Prognosis in Cutaneous Melanoma Patients. (22nd July 2015) - Donizy, Piotr; Zietek, Marcin; Leskiewicz, Marek; Halon, Agnieszka; Matkowski, Rafal
Abstract : ADAM-10 (CDw156, CD156c, and kuzbanian) is a protein belonging to a superfamily of metalloproteases, enzymes capable of degrading the extracellular matrix. ADAMs have also been shown to be primarily involved in ectodomain cleavage. The aim of the study was to assess the expression and intracellular location of ADAM-10 in 104 primary skin melanomas and 16 metastatic lesions from regional lymph nodes. Also, prognostic significance of ADAM-10 expression in primary tumor cells and metastatic lesion cells was evaluated during 5-year observation. It was revealed that high expression of ADAM-10 positive cells was strictly related with lower intensity of tumor-infiltrating lymphocytes (P = 0.037 ), which suggests that ADAM-10 regulates immunoresponse in melanoma initiation and progression. No statistically significant correlations were found between ADAM-10 expression in primary tumor cells and nodal metastases and other histopathological parameters analyzed. Decreased immunoreactivity of ADAM-10 in cancer cells from regional lymph nodes was correlated with worse prognosis; however this correlation was statistically nonsignificant (P = 0.065 ). Review of the literature shows that our study is the first one ever to describe the significance of ADAM-10 expression in correlation with detailed histopathological parameters of the primary tumor and data on long-term survival of cutaneous melanoma patients.